A gendered analysis of adaptive capacity and food security in Makueni County, Kenya - Phyllis Mumia Machio; Susannah M. Sallu; Betty Waized; Akwilina Wendelin Mwanri; Kwaku Gyebi Duodu (Frontiers in Sustainable Food Systems)
Climate change is expected to reduce crop and livestock productivity leading to increased hunger and food insecurity. Formulation of effective adaptation strategies can reduce the negative effects of climate change on food security. This study examined types of adaptation strategies implemented by males/male-headed households and females/female-headed households and how these influence food security. Food security was measured using Household Food Insecurity Access Prevalence (HFIAP) and probit model was used to estimate the effect of adaptation strategies on food security. Due to potential self-selection bias, this study also estimates Coarsened Exact Matching (CEM) model. Data was collected using structured questionnaires from 521 households and 1,049 adults from Makueni County, Kenya. Study findings indicated that approximately 72, 62, and 75% of households experienced reduced rainfall, less predictable rainfall and recurrent and prolonged droughts, respectively, to a large extent. The three most adopted adaptation strategies were conservation agriculture (69%), change of planting dates (49%), and planting of drought tolerant crops (47%). A higher share of male-headed households than female-headed households implemented all three adaptation strategies. Access to credit, non-farm income, types of crops grown, and weather perception variables were the important determinants of adaptation. We also found that planting drought tolerant crops and practicing conservation agriculture were associated with increased likelihood of food security but only for males/male-headed households. For female headed households, growing drought tolerant crops and changing planting dates reduced likelihood of food security while the effect of conservation agriculture was not statically significant. These findings provide evidence that adaptation to climate change provide potential for improvements in food security among males/male-headed households. This potential is however limited for female headed households. They are not only less likely to adapt but are also less likely to benefit from adaptation. These findings highlight women’s vulnerability to climate change and especially female-headed households and calls for policies that build women’s capacity to effectively adapt.